(untitled) (International Journal of Engineering and Computer Science, 2014)
In this project we are attempting to design a home that acts as an intelligent agent. This paper mainly focuses on developing a system which will automate all domestic devices. Datasets are built for analysis purpose. Voice is recorded and then converted in textual form. Then patterns of text are matched with the data sets provided. Data sets consisting of different conditions will be the initial input to the system. According to the input provided at given instant, corresponding action will be performed by the system.